Electrochemical Desorption of Thiolates and Sulfur from Nanoparticle and Planar Platinum Surfaces - Floridia Addato, María Alejandra (2013)
Thiolate-protected platinum nanoparticles have become promising for applications in heterogeneous catalysis and the fabrication of new materials for hydrogen storage. Once nanoparticles have been synthesized and conveniently grafted onto a particular support, thiol removal might be required before its use. Here, thiolate and sulfur electrodesorption from nanoparticle and planar platinum surfaces are comparatively studied by combining ex-situ X-ray photoelectron spectroscopy (XPS) and electrochemical techniques. We show that alkanethiolates and sulfur adsorbed on Pt surfaces are more stable against reductive desorption than these species on Au substrates. Furthermore, for short-chain thiol-capped platinum nanoparticles we observe complete removal of sulfur-containing species. Hence, these results make this procedure suitable for its use in electrocatalysis. As an example, we demonstrate that 2 nm thiomalic acid-protected platinum nanoparticles markedly improve the performance of a hydrogen storage alloy material, with no additional steps in the preparation of the electrodes.